Problems with editing and translating historical sources. Some Polish examples - Edward Skibiński (Fasciculi Archaeologiae Historicae, 2015)
Paper presents a new attitude to the issue of medieval editions of Latin written records and focuses on the importance of their publication in the form as close to the original version and its contents as possible. It also deals with some misunderstandings resulting from overinterpretation of sources which have not been carefully published and subsequently translated.